Analysis of the Distinction of Earnings Management between Islamic and Conventional Stocks Markets in the Consumer Goods Industry in Indonesia - Titin Agustin Nengsih; Nofrianto Nofrianto; Ahmad Syukron Prasaja; Sri Rahma; Nurfitri Martaliah; M. Taufik Ridho (Esensi: Jurnal Bisnis dan Manajemen, 2021)
Analysis of earnings management is carried out to achieve profit targets applied in financial statements management. This study analyzes the difference between earnings management in the consumer goods industry sector, Islamic and conventional stocks. Data is on financial statements and annual reports of manufacturing companies on IDX in 2016-2019 as many as 19 sharia and 10 non-sharia issuers. This research uses analysis of the independent samples test of earnings management, current tax burden, firm size, managerial ownership, and leverage both Islamic and Conventional stocks. The results show a significant difference in several variables in earnings management between two markets, i.e., Islamic and Conventional Stocks, which are current tax burden, managerial ownership, and leverage in manufacturing companies in the consumer goods industry in Indonesia in the period of 2016-2019